A new species and a new record of Neoperla Needham (Plecoptera: Perlidae) from Yunnan, China - Zeng, Liang-Liang; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2025)
A new species of the genus Neoperla Needham, 1905, N. spinistrumata sp. nov., is described from Yunnan Province, China. Neoperla lahu Stark, 1983, another species previously known only from Thailand, is recorded for the first time in China. Based on the morphological characteristics of the penis, N. lahu is placed into the lushana-group in this paper, and a clear color image of this species is provided for the first time.